Teaching Community On and Off Campus: An Intersectional Approach to Community Engagement. Issue 157 (March 2017) - Mitchell, Tania D.
Abstract : The author explores how taking an intersectional approach to the analysis of social problems, identity, and planned interventions can enhance service learning programs and student preparation for community engagement.